Effect of commonly used irrigants on the colour stabilities of two calcium-silicate based material - Kulvinder Singh Banga; Trusha Shah (Istanbul University, 2019)
Purpose: The aim of present study was to evaluate the color stability of calcium-silicate based cements (CSC) Mineral Trioxide Aggregate (MTA) and BiodentineTM when exposed to endodontic irrigating solutions 5% Sodium hypochlorite (NaOCl) or 2% Chlorhexidine (CHX). Materials and Methods: A total of 60 (n=30) cylindrical samples (10 mm diameter, 2 mm height) were prepared by manipulating white MTA Angelus (Angelus, Londrina, PR, Brazil) and BiodentineTM (Septodent, Saint Maur, France) according to manufacturer's instructions. These samples were immersed in 5% sodium hypochlorite (Prime Dental Products Pvt. Ltd.,Mumbai, India), 2% chlorhexidine gluconate (Dentochlor, Saronno VA, Italia), or distilled water for 24 hours. Color changes were measured using UV spectrophotometer (UV-1650, Shimadzu, Europe) and the values were tabulated. Results: A significant difference was observed between group I and II with respect to both parameters A & B (p